Comprehensive Analysis of Novel Synergistic Antioxidant Formulations: Insights into Pharmacotechnical, Physical, Chemical, and Antioxidant Properties - Sorinel Marius Neacșu; Magdalena Mititelu; Emma Adriana Ozon; Adina Magdalena Musuc; Izabela Dana Maria Iuga; Bogdan Nicolae Manolescu; Simona Petrescu; Jeanina Pandele Cusu; Adriana Rusu; Vasile-Adrian Surdu; Eliza Oprea; Dumitru Lupuliasa; et al. (MDPI AG, 2024)
(1) Background: Oxidative stress plays a pivotal role in the pathogenesis of various diseases, including neurodegenerative disorders, cardiovascular diseases, cancer, and diabetes, highlighting the pressing need for effective antioxidant interventions. (2) Methods: In this study, we aimed to develop and characterise two novel antioxidant formulations, F3 and F4, as therapeutic interventions for oxidative stress-related conditions. (3) Results: The physicochemical characterisation, preformulation analysis, formulation, preparation of filling powders for capsules, capsule content evaluation, and antioxidant activity assessment of the two novel antioxidant formulations were assessed. These formulations comprise a combination of well-established antioxidants like quercetin, biotin, coenzyme Q10, and resveratrol. Through comprehensive testing, the formulations' antioxidant efficacy, stability, and potential synergistic interactions were evaluated. (4) Conclusions: The findings underscore the promising potential of these formulations as therapeutic interventions for oxidative stress-related disorders and highlight the significance of antioxidant interventions in mitigating their progression.